(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The research results of studying the loadsacting on hydraulic cylinders of the working equipment control mechanism depending on the parameters of its positioning. Keywords:motor-grader, hydraulic cylinders , loads.